Provenance change of sediment input in the northeastern foreland of Pamir related to collision of the Indian Plate with the Kohistan‐Ladakh arc at around 47 Ma. Issue 2 (12th February 2016) - Sun, Jimin; Xiao, Wenjiao; Windley, Brian F.; Ji, Weiqiang; Fu, Bihong; Wang, Jiangang; Jin, Chunsheng
Abstract: The Pamir plateau forms a prominent tectonic salient that marks the western end of the Himalayan orogen containing several terranes that were accreted to Eurasia from the Late Paleozoic to Cenozoic. A detailed knowledge of the tectonic evolution of the Pamir salient during the Cenozoic is important for our understanding of the intracontinental deformation in the western Himalaya. Although the tectonic evolution of the Pamir salient has long been studied, the timing of collision between the Indian Plate and the Kohistan‐Ladakh arc is still a matter of debate. We present new U‐Pb ages and Hf isotopes of detrital zircons, magnetic fabrics, and stable isotopes from the foreland basin on the northeastern margin of the Pamir that indicate a change in sediment provenance started at about 47 Ma. Sediments in the southwest Tarim Basin were partially derived from the uplifted and eroded Karakoram and Kohistan terranes created by the collision between the Indian Plate and the Kohistan‐Ladakh arc at circa 47 Ma, as a result of northward thrusting and propagation of the Indian Plate under Eurasia. Key Points: Provenance change in the northeastern foreland of the Pamir salient at 47 Ma Collision between the Indian Plate and the Kohistan‐Ladakh arc around 47 Ma Tectonic evolution in Pamir control source material accumulation in its foreland